The influence of instagram on korean-style fashion trends among college students - Atika, Anjelir Fara; Suminar, Panji; Widiyarti, Diyas (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to examine the impact of Instagram social media on the dress style of students of the University of Bengkulu. The research approach uses descriptive qualitative studies. This study uses a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews, participant observations, and documentation of Instagram uploads. The purposive sampling technique was used to select relevant participants, namely active students aged 18–25 years from three faculties at the University of Bengkulu (Faculty of Law, Faculty of Economics and Business, and Faculty of Social and Political Sciences) who actively use Instagram and often post fashion-related content. Data analysis was carried out using the Miles and Huberman method, which included data reduction, data presentation, and conclusion drawn, as well as triangulation to increase the validity of the findings. In sociological analysis, rational choice theory is used to understand how students adapt fashion trends on Instagram by considering various factors such as suitability, financial ability, and social acceptance. The findings show that Instagram is the main source of inspiration for students in determining their dressing style, especially related to Korean style trends. Nonetheless, students demonstrate critical ability to select and modify these trends to suit personal preferences and socio-cultural contexts. Students develop a variety of adaptive strategies, from financial management to negotiation with environmental norms, to express a unique yet relevant fashion identity. It is hoped that this research will contribute to a broader understanding of the role of social media in shaping student identities and behaviors in the digital era.